Intimate partner violence and sexual and gender diversity in Spanish legislation - Mónica Laliga Mollá (Oñati Socio-Legal Series)
The criminal justice system responds to gender-sex minority dating violence differently from violence in heterosexual couples, as far as national law in Spain is concerned, although it does receive specific mention in regional legislation. Research shows that violence in heterosexual couples shares characteristics in common with that which takes place in sexual minorities, from its prevalence to risk factors, some of them associated with the gender rules that surround affective-sexual relationships. There are also differences, however, and risk factors that are specific to violence in LGBTIQ+ couples. The aim of this paper is to analyze how such abuse is currently treated according to national and regional legislation prior characterization of this violence. Research shows the difficulties and limits of Spanish legislation to address this type of violence. In order to improve the way these problems are dealt with, the implications of the intersectional feminist perspective should be taken into account.